DEFORMATION MECHANISMS, TIMING AND SHEAR SENSE ANALYSIS OF PART OF THE PRECAMBRIAN TERRAIN OF SOUTHWESTERN NIGERIA - Adedoyin, A. D; Ebiri, E. P; Alebiosu, M. T (university of el oued/جامعة الوادي, 2019)
The study area is part of the polycyclic Precambrian Basement Complex of southwestern Nigeria, which comprises meta-sediments and granitoids of varying compositions. The area was primarily deformed into a large-scale sheeted structure, which was sequentially followed by developments of first and second phases of folding that interfered with each other. Brittle to semi-ductile shear deformations, initiated by an ESE-directed transport of the hanging wall of a major NE-SW trending low-angle normal fault culminated in the third phase of fold and development of widespread shear zones. Latter phases of deformation resulted in rotation of finite strain axis relative to the instantaneous strain during a non-coaxial progressive simple shear deformation. We posit that the dominant terminal mechanism of deformation in the area is the late-kinematic progressive heterogeneous simple shear during the late- to post-Pan African orogenesis.
Article
Keywords: Shear; deformation; tectonic; poikiloblast; rotation; isoclines.